PENGARUH MEDIA PEMBELAJARAN PLATFROM MICROBLOGGING TUMBLR TERHADAP KEMAMPUAN MENULIS TEKS BIOGRAFI SISWA KELAS X SMK NEGERI 2 MEDAN - Rumada Siregar; Harlen Simanjuntak; Martua Reynhat Sitanggang Gusar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the effect of using the Tumblr microblogging platform learning media on the ability to write biographical texts of class X students of SMK Negeri 2 Medan. This study is a quantitative study, using a pre-experimental design in the form of One-Group Pre-test and Post-test Design. The research population was 125 people and the sample was 25 people, which was determined by random sampling techniques. The analysis techniques used were Normality Test, Homogeneity Test, and Hypothesis Test. After conducting the research, namely the influence of the Tumblr microblogging platform media in the pre-test with the lowest value of 50 and the highest value of 75 with an average value of 61.24. Then the influence of the Tumblr microblogging platform media in the post-test with the lowest value of 62.5 and the highest value of 87.5 with an average value of 75.68. The average post-test score was 75.68 and the average pre-test score was 61.24. This indicates that the Tumblr microblogging platform significantly impacted students' biographical writing skills. This is evidenced by the results of hypothesis testing and data analysis, which yielded a Tcount ˃ Ttable of 8.64 > 2.05. Thus, the hypothesis is accepted.